Hubungan Kebisingan dengan Kadar Glukosa Darah pada Manusia : Sebuah Review - Flora Rumiati; Alfredo Lasiata Lailossa; William William; Susanty Dewi Winata (Jurnal MedScientiae, 2022)
Noise is a sound whose presence is unwanted that it has an impact on health problems, an uncomfortable environment and can cause deafness. The impact of noise on health can occur in workplace and cause disturbances that are classified in stages. Several studies have found that sudden exposure to sound causes physiological reactions such as pulse, blood pressure, metabolism, sleep disturbances and constriction of blood vessels. The search for research journal articles was obtained from publication media, filtered from inclusion and exclusion criteria and obtained 10 journals to be reviewed. The results of this study are that in all the articles reviewed by the author there is a relationship between long-term noise exposure and human blood glucose levels. Noise exposure led to increased phosphorylation of jnk (c-Jun N-terminal kinase) as well as decreased phosphorylation in skeletal muscle in response to exogenous insulin stimulation, and another result was that plasma levels of TNF-α and IL-6 in skeletal muscle increased after long-term noise exposure. Noise exposure also causes dysregulation of the activity of the hypothalamo-pituitary adrenal axis with high corticosterone, which appears to blunt insulin action in peripheral tissues, consequently limiting glucose uptake and glycogen deposition in the liver and gastrocnemius muscle.